The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

L'équilibre contractuel - Muggeo, Marine-Alice (Université de Toulon, 2017)
Ces dernière années, le concept d'équilibre contractuel est devenu omniprésent dans notre droit et se retrouve dans quasiment toutes les disciplines du droit. L'équilibre contractuel n'a donc eu de cesse de se renforcer (Titre 1) dans diverses disciplines, car le droit des contrats est une matière transversale. On retrouve donc cette notion autant dans les contrats spéciaux que dans le droit commun des contrats. Ainsi une fois étudié, cet équilibre se retrouve dans les différentes phases de construction et d'exécution du contrat (Titre 2). C'est une partie qu'il faut appréhender car cela nous permet de comprendre où se retrouve l'équilibre dans le contrat. Et constater que c'est une notion centrale qui se retrouve dans l'ensemble des phases pré-contractuelles et contractuelles.
Keywords: Contrats d'affaires; Contrats informatiques; Contrats spéciaux; Crédit consommation; Droit des contrats; Honoraires avocats; Sécurité juridique

L'étendue de la compétence ratione materiae du juge étatique dans le règlement des différends nés de l'exécution d'un contrat complexe - Djemba Kandjo, Joseph (Université de Montréal, 2015)
Les arrêts sur l’affaire Beaudoin c. Université de Sherbrooke (Cour Supérieure et Cour d’Appel du Québec 2008-2010) ont porté sur l’intensité de l’obligation de consultation insérée dans l’accord de partenariat de recherche. Ce type de partenariat est souvent créé par un accord et peut prendre plusieurs formes. La plupart d’entre elles sont méconnues par le droit, c’est pourquoi la doctrine les considère comme étant des entreprises complexes puisque le choix des partenaires est souvent guidé par le souci d’échapper au formalisme qu’imposent les règles étatiques. Cependant, les pratiques connues dans le secteur d’activité des associés et les accords qui les lient sont souvent les seules règles qu’ils suivent. En cas de conflit, ils recourent généralement à un tiers expert pour régler leur litige, la saisine des tribunaux ne se faisant qu’exceptionnellement. Dans cette cause, les contractions entre les deux décisions ont soulevé quelques interrogations : d’une part, sur la capacité des tribunaux à trancher des conflits qui peuvent naître au cours de l’exécution de ce type de contrat, et d’autre part sur la compatibilité des règles matérielles applicables au fond par les juges lorsque les parties ne sont liées que par la lex contractus et les usages reconnus dans leur secteur d’activité. Cette étude tente donc d’identifier la forme de partenariat en cause afin de mesurer l’étendue de la compétence ratione materiae du juge dans la résolution des conflits nés d’un contrat complexe (PARTIE I), et d’examiner l’opportunité de recourir aux modes alternatifs de résolution des litiges (PARTIE II). The decision in the case Beaudoin v. Université de Sherbrooke (Superior Court and Quebec's Court of Appeal 2008-2010) examines the extent of the obligation to consult in a research partnership agreement. This kind of partnership is often created through agreements and can take several forms. The majority of those are unknown to the law; this is why the doctrine considers them to be complex enterprises, since the choice of the partner is often guided by the will to curtail the formalism imposed by State rules. Familiar practices used in the relevant field and the agreements which link them are often the only rules they respect. In case of dispute, they generally seek a third party expert to settle the dispute and only exceptionally resort to national courts. In this specific case, the contractions present the decision raise some important questions: on one hand, the capacity of the courts to solve conflicts which arise from the execution or interpretation of this sort of partnership, and on the other hand the compatibility of material rules applicable to the subject matter by judges to parties often bound by lex contractus and the usages applicable in their field of activity. This study tries to identify the form of partnership applicable in this case in order to measure the extent of the ratione materiae competence of the judge in the settlement of a dispute arising from the execution of a complex contract (PART I), and to examine the possibility of recurring to alternative forms of dispute settlement for disputes of this nature (PART II).
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/11876/Djemba-kandjo_Joseph_2014_memoire.pdf
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Commercial; Commerciaux; Compétence; Différend; Dispute; Joint-venture; Judge; Juge; Lex; Material; Matérielle; Mercatoria; Political Science; Usages

Acentenin ücret hakkı - Kizilay, Aygül (Kocaeli Üniversitesi, 2015)
6102 sayılı TTK acentelik alanında önemli yenilikler getirmiştir. Yeni kanun 6762 sayılı Kanunda yer almayan bazı kurumlara yer vermiş, eski kanun döneminde uygulamada sorunlara yol açan bazı hükümler ise gözden geçirilmiştir. Acentelik sözleşmesi tam iki tarafa borç yükleyen sözleşme olduğundan, acentenin gördüğü iş için her zaman bir ücret talep etme hakkı bulunmaktadır. Acentenin en önemli hakkı olan ücret hakkı, müvekkilin karşı edimi olarak kendisini gösterir. Ücret hakkını düzenleyen hükümler arasında ücrete hak kazandıran işlemler ve ücrete hak kazanma zamanı ile ilgili hükümler yeniden ele alınmıştır. Bunlarla birlikte ücret hakkıyla ilgili olarak acenteye çok geniş bir bilgi alma ve defter kayıtlarını isteme ve inceleme hakkı tanınmıştır. Çalışma "Giriş" ve "Sonuç" bölümleri haricinde üç bölümden oluşmaktadır. Birinci bölümde acente kavramı ve bu kavramı oluşturan unsurlar incelenmiştir. Ayrıca acentenin hak ve borçlarına değinilmiştir.Çalışmanın ikinci bölümünde, acentenin en temel hakkı olan ücret hakkı incelenmiş olup; üçüncü bölümde ise, 6102 sayılı TTK ile getirilen düzenlemeler ve değişiklikler, 6762 sayılı TTK ile karşılaştırmalı olarak ele alınmıştır. Ücret hakkına ilişkin bu değişiklikler, acentelik sözleşmesi sona erdikten sonra acentenin ücret talep edebileceği haller; ücrete hak kazanma anındaki ve ücretin muaccel olacağı andaki değişiklikler; ücret hakkında acentenin belge ve bilgi isteme hakkının emredici olarak düzenlenmesi olarak özetlenebilir. Law no. 6102 Turkısh Commercial Code brings advances at provisions about agency .The new Code brings new provions comparing with Law no. 6762 Turkısh Commercial Code. Furthermore, it resolves some issues existing in the period of 6762 Turkısh Commercial Code. Agency contract is a bilateral contract. Therefore the rights of the agent, constitutes theobligations of the principal. The commission right is also obligation of the principal. The provisions about commission right are reargued out, including transactions which bearing commission and time of entitlement of commission This thesis is consist of three chapters excluding the "introduction" and the "conclusion" parts. In first chapter, the notion of the agent and the elements of this notion are discussed. Moreover, rights and obligations of agent are examined. In chapter two, the principal right of agent, commission right is discussed. In chapter three, commission right is examined comparing with the provisions of Law no. 6102 Turkısh Commercial Code and Law no. 6762 Turkısh Commercial Code. Amendments about commission right are time of entitlement of commission , time of commission becoming payable. Furthermore , in some cases, an agent shall be entitled to commission on commercial transactions concluded after the agency contract has terminated. Lastly, an agent shall be entitled to demand that he be provided with all the information, and in particular an extract from the books, which is available to his principal and which he needs in order to check the amount of the commission due to him. Provision about demanding information is statutory.
433640
Keywords: Acenteler; Agents; Commissions; Kanunlar 6762 sayılı; Komisyonlar; Laws 6762 numbered; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Wage policies; Wage systems; Ücret politikaları; Ücret sistemleri

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

La résolution du contrat de vente en droit OHADA : d’une réforme à l’autre - Ebata, Rodrigue N. (Université de Montréal, 2014)
La présente étude examine une des difficultés que soulève la résolution du contrat de vente en droit africain des affaires. L'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) créée par le Traité du 17 octobre 1993 organise les règles communautaires relatives à la résolution du contrat de vente. Le Livre VIII de l’Acte uniforme OHADA portant sur le Droit commercial Général a été adopté le 15 décembre 2010 et a abrogé l’Acte du 17 avril 1997. Selon l’article 281 de l’Acte uniforme, la résolution du contrat de vente ne survient que lors de l’inexécution totale ou partielle de l’obligation du cocontractant. Notre étude visera à évaluer les conséquences dans le droit de la vente OHADA de la substitution du critère de privation substantielle par celui de la gravité du comportement du débiteur justifiant une résolution unilatérale du contrat. Cette nouvelle position du droit de la vente OHADA se démarque dans une certaine mesure du droit matériel uniforme et rejoint un courant adapté aux impératifs socioéconomiques du commerce tant régional qu’international. En outre la partie lésée devra déterminer la gravité du comportement du débiteur au risque de voir sa demande sanctionnée pour défaut de droit et donner lieu à des dommages intérêts à l’autre partie. En effet, avec pour optique la nécessité de sauvegarder le contrat au nom du principe favor contractus, comment le juge détermine a posteriori si la gravité du comportement du cocontractant est suffisante pour anéantir le contrat? Ce nouveau critère de la gravité du comportement du cocontractant en droit de la vente OHADA vient supplanter le critère de la privation substantielle et fait cohabiter la traditionnelle résolution judiciaire avec celle de la résolution unilatérale dont les contours demeurent incertains. Les cas d’ouvertures liés à la résolution du contrat de vente OHADA pour inexécution des obligations fondamentales ou accessoires seront passés au crible de même que leurs effets sur les parties. Dans une approche comparatiste avec la Convention de Vienne et les règles de codifications privés telles que les Principes UNIDROIT ou du Droit Européen des Contrats il y a lieu de s’interroger sur la mise en œuvre et les conséquences de la résolution du contrat de vente OHADA par l’inexécution de l’obligation d’une des parties due à un manquement essentiel d’une part et à la gravité du comportement du débiteur d’autre part. The Treaty on Harmonisation of Business Law in Africa signed on October 17th, 1993 created the Organisation for Harmonisation of Business law in Africa (OHBLA).OHBLA organises common rules on resolution of sales contracts. The Book VIII of the Uniform act on General Commercial Law adopted on December 15th, 2010 replaces the previous act of April 17th, 1997. According to article 281 of this uniform act, contract resolution only occurs when there is a partial or total non execution of one party’s obligation. The present study is going to examine one of the difficulties that exist in the resolution of sales contracts in African business law. Our study will consist in evaluating the consequences of substitution of the substantial privation criteria by the seriousness of the debtor’s behaviour in OHBLA sales law. This substitution justifies a unilateral contract termination. This new OHBLA law position somehow distinguish itself from material uniform law and joins a new position socioeconomically more adapted to regional and even international business. Moreover, the prejudiced party will have to determine the gravity of the debtor’s behaviour risking to be punished for lack of motives and according damages to the other party. In fact, in order to save the contract by all means according to the favor contractus principle, how will the judge subsequently determine if the debtor’s behaviour gravity is enough to breach the contract? This new criterion of the gravity of a contracting party’s behaviour comes in replacement of the substantial privation criteria and enhances the cohabitation of the traditional judiciary termination and the unilateral cancellation which is still uncertainly defined. Cases related to contract resolution caused by non-execution of mandatory or accessory obligations in OHBLA law will be carefully examined as well as their effects on contracting parties. In a comparative approach with the Vienna Convention and private codifications such as UNIDROIT principles or European contract law, we will wonder about the use and the consequences of resolution of sales contract in OHBLA law caused by non-execution a mandatory obligation on one part and the gravity of one party’s behaviour on the other part.
Keywords: African law; Business law; CISG; CVIM; Commerce international; Commercial law; Contract; Contrat; Contrats internationaux; Droit africain; International business; International sales; OHADA; OHBLA; Resolution; Résolution; Sales; Sales law; UNIDROIT; Vente; Vente internationale

Da admissibilidade do direito de retenção no contrato de empreitada de construção imobiliária - Correia, Armando Francisco Gonçalves (Universidade Católica Portuguesa, 2013)
Keywords: Construction immobilière; Contrat; Droit de rétention; Immeuble (construction)

O direito de retenção do empreiteiro na empreitada de construção de imóveis - Nunes, Fernando Jorge da Costa Mota (Universidade Católica Portuguesa, 2012)
Keywords: Construction immobilière; Contrat; Droit de rétention; Immeuble (construction)

Commercial law reform in Africa: a means of socio-economic development, but for whom? Perspective of women entrepreneurs in Benin - Deschamps, Isabelle (McGill University, 2011)
This thesis explores the interactions between French and foreign influenced formal commercial law in the Republic of Benin and women's on-the-ground business practices. It uses a comparative, historical and inter-disciplinary and empirical methodology (Clinical legal pluralism). It contributes to the debate on the relationship between law and socio-economic development in African States where formal law is modeled on that of their former colonizing power. The dissertation looks at the evolution of business law and of economic activity in the region from pre-colonial times to present where OHADA Uniform Acts ("Acts") largely inspired by French and foreign law constitute Beninese formal commercial law's primary source. The thesis then examines elements of businesswomen's socio-cultural realities and economic practices in the region to assess the extent to which they are accounted for in formal law. The analysis reveals the considerable gap that continues to exist between the Western-inspired Acts and the realities and modes of Beninese women entrepreneurs. While the OHADA regime may benefit French and other foreign companies that contribute to the region's economic vitality to varying extents, the difficult appropriation and access by a majority of citizens and enterprises in Benin to OHADA laws prevent Beninese (in particular female) small and medium enterprises from playing a greater role in the socio-economic development of their countries. The dissertation suggests that the paradigms and methods currently used by OHADA and international organizations such as the World Bank in their law reform activities do not take appropriate account of economic, social and cultural realities of the regions where the new law is to be implemented. These include gender issues in business practices. It argues that commercial law reformers should recognise the central role of citizens in creating the law. Finally, it outlines an analytical framework for applying these objectives so as to empower citizens in Benin as lawmakers. This framework will integrate some of existing law reform paradigms with additional ones focused on the identity of legal actors in the region (banks, small, medium and large entrepreneurs, micro-credit institutions, financiers, etc.), the dynamics between them, the role of women in business and alternative legal reform methods based on bottom-up approaches to law. Ce mémoire s'intéresse aux interactions entre le droit commercial d'inspiration française ou étrangère dans la République du Bénin avec les réalités pratiques que les femmes commerçantes y vivent sur le terrain. Une méthodologie comparative, historique et interdisciplinaire y est employée (pluralisme juridique clinique). Il se veut une contribution au débat sur la relation entre le droit et le développement socio-économique dans les États Africains où le droit formel prend modèle sur celui de leur ancienne métropole.L'auteure débute en examinant l'évolution du droit des affaires et de l'activité économique dans la région à partir de l'époque précoloniale jusqu'à aujourd'hui, où les Actes Uniformes OHADA (les « Actes »), fondés largement sur le droit Français et étranger, constituent la source la plus importante du droit commercial Béninois.Elle poursuit en explorant les réalités socioculturelles et les pratiques économiques des femmes commerçantes dans la région afin de vérifier dans quelle mesure elles sont prises en compte par le droit formel. Cette analyse révèle un écart considérable qui perdure entre les Actes d'inspiration occidentale et les réalités et pratiques des femmes commerçantes Béninoises.Bien que le régime OHADA puisse bénéficier aux investisseurs Français et étrangers qui contribuent, à divers degrés, à l'activité économique dans la région, la difficulté pour une majorité de citoyens et d'entreprises Béninois à s'approprier ou accéder aux Actes empêchent les petites et moyennes entreprises Béninoises (particulièrement celles dirigées par des femmes) de jouer un plus grand rôle dans le développement socioéconomique de leur pays.L'auteure postule que les paradigmes et méthodes employés par l'OHADA ainsi que par des organisations internationales telles la Banque Mondiale dans le cadre de leurs activités de réforme législative ne tiennent pas suffisamment compte des réalités économiques, sociales et culturelles des régions où leurs réformes sont mises en œuvre. Ces réalités comprennent les questions liées au genre dans le cadre des pratiques commerciales. L'auteure suggère que les réformateurs du droit commercial reconnaissent davantage le rôle central que les citoyens jouent dans la création du droit.Enfin, le mémoire trace les contours d'un cadre analytique qui applique ces objectifs de façon à réhabiliter les citoyens Béninois à titre de créateurs de droit. Ce cadre intègre quelques-uns des paradigmes existants sur la réforme du droit avec de nouveaux paradigmes centrés sur l'identité des acteurs juridiques dans la région (les banques, les petites, moyennes et grandes entreprises, les institutions de microcrédit, les investisseurs, etc.), les dynamiques entre eux, le rôle des femmes dans le milieu des affaires et les méthodes alternatives de réforme législative fondées sur une approche juridique du bas vers le haut.